Economic Pressure and Debt Decision-Making of the Customer's Family Bank Keliling/Bank Emok: Economic Pressure and Debt Decision-Making of the Customer's Family Bank Keliling/Bank Emok - Ranti Rosanti; Euis Sunarti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Difficult economic conditions often force families to borrow money from bank keliling/bank emok. This study analyzes the effect of family characteristics, debt characteristics, economic pressure before debt, and debt decision-making on economic pressure after debt. In particular, this study distinguishes economic pressures before and after debt. The research design used is a retrospective and cross-sectional study involving 60 wives of customers of bank keliling/bank emok selected by simple random sampling. This research is located in Pulosari Village and Margamekar Village, Pangalengan District, Bandung Regency, West Java. The correlation test results show a significant positive relationship between objective economic pressure before debt and debt decision-making. Debt decision-making is positively related to objective and subjective economic pressure after debt. The economic pressure after the debt is higher than before the debt. This study concludes that the higher objective economic pressure before debt and the greater reason for debt, the higher economic pressure after debt. The study results show the importance of families raising awareness about the risks of debt so that there is no increase in economic pressure.